Surgical and functional remodeling of the tibial articular surface in cases of pilon fractures - Bets, Iryna; Stoyko, Ivan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Results of treatment of pilon fractures largely depend on the quality of restoration (remodeling) of the tibial articular surface. The most difficult are destructive (impresive) intraarticular fractures of types B and C in which in surgical treatment they traditionally use technologies of open reposition and internal plate fixation together with bone autoplasty or using of artificial materials. These operations are very dangerous because of complications and severe to foreseeing about loss of articular surface and reducing the risk of osteoarthritis. Objective: To assess the remodeling of the tibial articular surface after pilon fractures with help of physiological surgical technique and early functional treatment. Methods: We analyzed the results of treatment in 22 patients with fractures type B (10) and type C (12). All patients were treated with help of original technique of surgical remodeling based on the use of distractive ligamentotaxis by means of unilateral rod devices in combination with elements of reposition osteosynthesis. Conditions for early functional treatment (prevention of secondary displacements) are provided by means of functional orthoses proposed by authors and made of plastic materials. Results: in 64% cases it was possible anatomically to reconstruct the tibial articular surface by means of distraction ligamentotaxis. In 36 % cases when the articular surface after surgery was partly restored we administered an early functional treatment. Conclusion: The tactics of treatment in cases of pilon damages when using physiological methods of surgical reposition and fixation of fragments combined with early functional treatment allows in the most patients for remodeling the tibial articular surface.